MODEL PENGEMBANGAN PROFESIONALISME GURU BERBASIS ISLAMIC EDUCATIONAL MANAGEMENT: SEBUAH LITERATURE REVIEW - Nabila Luvianingtias, Shera; Lestari, Rahayu; Sri Anggoro, Bambang; Mas Ayu, Sovia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teacher professionalism is a crucial factor in improving educational quality, particularly in Islamic educational institutions that require a balance between professional competence and Islamic values. This study aims to analyze and synthesize various teacher professionalism development models based on Islamic Educational Management through the Systematic Literature Review (SLR) method. Data were collected from scholarly articles indexed in Google Scholar, Scopus, DOAJ, Crossref, and Garuda published between 2021 and 2025. The selection process involved identification, screening, eligibility assessment, and inclusion stages, resulting in 35 articles that met the established criteria. The findings indicate that effective teacher professionalism development models encompass four main themes: Continuous Professional Development (CPD), Islamic leadership and Islamic academic supervision, Islamic organizational culture, and the integration of technology and instructional innovation. These models contribute to enhancing teachers’ pedagogical, professional, social, and personal competencies while strengthening moral integrity, spirituality, and an Islamic work ethic. The study concludes that the most effective approach to teacher professionalism development is an integrative model that combines continuous competency development, leadership and supervision grounded in Islamic values, Islamic organizational culture, and the systematic and sustainable digital transformation of learning.